Ethics and deontology of medical education and nurses in Portugal - Oliveira, Clara Costa (2012)
This article discusses deontological issues of health care professions in relation to their ethical foundation. We present four models of teaching ethics and deontology in doctors’ training and the results of a PhD research on the teaching of these subjects in nurses’ training in Portugal. Given the importance of bioethics in deontological training of health care professions, we present a comparative analysis of. bioethical principles enunciated by Beauchamp and Childress (1979), related to ‘ethics of justice’, and Kemp’s(2000) proposal, associated to an ‘ethics of care’. Given the ambiguity of these bioethical expressions, we focus on the analysis of its contents and the need to discuss the fundamentals of ethical training of doctors and nurses in relation to the ethical theories they are derived from. Utilitarian ethics, duty ethics, virtue ethics, when the analysis of bioethics’ fundaments is not trained, the duty of caring of suffering can be put at risk.